Miljögifters exponering, ackumulering och effekter på immunsystemet hos husdjur - Hollstedt, Sofia (2008)
The purpose of this literature review was to describe the paths of exposure and accumulation of organic pollutants into the tissues of farm animals. Organic pollutants can be spread in the environment by air and rainwater. Farm animals can be exposed to these pollutants for example by eating soil or contaminated plants. Many of the pollutants can then accumulate in the fat tissues of the body because of their lipophilic character. Brominated flame retardants and perfluorolated compounds are both pollutants of current interest. Both of them are persistent and have negative effects on the environment, animals and human beings. Their concentration in the environment show no sign of decreasing, some compounds are even increasing. One system affected by many environmental pollutants is the immune defence, e.g. thymus atrophy can be developed. The knowledge of the toxic effects on the immune system is however limited for many environmental pollutants. In conclusion, this review shows that soil is the most important pathway of exposure for organic pollutants and that the accumulation of the pollutants mostly occure in the fat tissue. For a more efficient deduction of the effects of organic environmental pollutants on the health and production of farm animals, more knowledge is required regarding the effects on the immune system of environmental pollutants.